Engineered polymer nanoparticles with unprecedented antimicrobial efficacy and therapeutic indices against multidrug-resistant bacteria and biofilms - Gupta, Akash; Schnurr, Martin (Journal of the American Chemical Society, 2018)
The rapid emergence of antibiotic-resistant bacterial “superbugs” with concomitant treatment failure and high mortality rates presents a severe threat to global health. The superbug risk is further exacerbated by chronic infections generated from antibiotic-resistant biofilms that render them refractory to available treatments. We hypothesized that efficient antimicrobial agents could be generated through careful engineering of hydrophobic and cationic domains in a synthetic semirigid polymer scaffold, mirroring and amplifying attributes of antimicrobial peptides. We report the creation of polymeric nanoparticles with highly efficient antimicrobial properties. These nanoparticles eradicate biofilms with low toxicity to mammalian cells and feature unprecedented therapeutic indices against red blood cells. Most notably, bacterial resistance toward these nanoparticles was not observed after 20 serial passages, in stark contrast to clinically relevant antibiotics where significant resistance occurred after only a few passages.
Gesehen am 15.08.2019